2009
DOI: 10.1002/maco.200905500
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption effect of 1‐((2‐hydroxynaphtalen‐1‐yl) (phenyl)methyl)urea on the carbon steel corrosion in hydrochloric acid media

Abstract: The adsorption effect of 1-((2-hydroxynaphtalen-1-yl)(phenyl)methyl)urea (HNPU) on corrosion behavior of carbon steel in 1 M hydrochloric acid solution was investigated using weight loss, potentiostatic polarization, and infrared spectroscopy methods. Surface morphology was studied by scanning electron microscopy (SEM). The experimental results, suggest that HNPU inhibited the corrosion of carbon steel in acid solution and the inhibition efficiencies increased as the concentration of the compound in the soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…11 The value 55.5 in the above equation is the molar concentration of water in solution [36,37]. Thermodynamic parameters for adsorption process obtained from Langmuir's adsorption isotherm for the studied inhibitors are given in Table 4.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…11 The value 55.5 in the above equation is the molar concentration of water in solution [36,37]. Thermodynamic parameters for adsorption process obtained from Langmuir's adsorption isotherm for the studied inhibitors are given in Table 4.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Theoretical values of Fe = 7 eV and Fe = 0 eV can be used to calculate the amount of electron transfer from organic inhibitors to Fe metal surfaces. The inhibition efficiency value obtained from the electron donation of organic inhibitors to Fe metal coincides with the electron transfer value [37]. Organic inhibitors' ability to give electrons can do so to mild steel's surface (Fe 110).…”
Section: Resultsmentioning
confidence: 55%
“…Progress in this field has revealed that corrosion inhibition is affected by several factors such as nature of the metal, the type of corrosive material, and the structure of the chemical composition used as an inhibitor which is directly related to its adsorption efficiency at the metal or alloy surface . Corrosion of metal and alloys causes a lot of annual financial loss to industries, for this reason, extensive research has been carried out on the factors affecting corrosion reduction . Among the various possibilities used to prevent corrosion are compounds that are adsorbed on the metal surface, blocking the metal from contact with the corrosive solution.…”
Section: Introductionmentioning
confidence: 99%